Species identity, richness and developmental stage of morphology affect enzymatic activiy of the soil microorganisms in arid Patagonia, Argentina - Cardillo, Daniela Solange (2019)
Microbial communities are a key for terrestrial ecosystem functioning. However, their responses to changes in plant species identity and richness, and stages of developmental morphology have been rarely investigated. The objective of this study was to evaluate the impact of the identity, richness and stage of developmental morphology of plant species on soil microbial communities throughout the enzymatic activity of the dehydrogenase. Studies were conducted under wild, field conditions, and on field experimental plots having different species richness. Treatments included a control (intraspecific monocultures) or combinations of 2, 4, or 6 species pertaining to different functional groups (i.e., perennial either grasses or herbaceous dicots or shrubs). The grass Nassella tenuis and the shrub Larrea divaricata showed a lower (p<0.05) activity of the dehydrogenase than most of the other studied species under wild, field conditions. The enzymatic activity of the dehydrogenase was either similar or greater (p<0.05; e.g., Amelichloa ambigua, L. divaricata), but not lower, as species richness increased in the reproductive stage of developmental morphology. Finally, the dehydrogenase activity was in general greater (p<0.05) at the reproductive (late spring) than vegetative (late fall) stage of developmental morphology in all studied species. These results indicate that species identity, richness and stage of developmental morphology might be important determinants of the degree of microbial activity in the soil.